Development of civic digital book based on pancasila student profile as strengthening student citizenship character - Aryanti Dwi Untari; Lina Marlina (Universitas Tanjungpura, 2023)
This research is very important to carry out in the context of developing a digital PPKn textbook based on Pancasila student profiles for secondary level schools. Until now, many researchers have studied the themes of PPKn textbooks in terms of their values and content, but have not touched on the contents of the Pancasila student profile. The aim of this research is to strengthen the civic character of students at SMA IT Al-Izzah Ciruas District. Attack through the development of digital PPKn textbooks based on Pancasila student profiles. This research developed a digital PPKn textbook based on Pancasila student profiles in the form of a Flipbook. In practical terms, it is hoped that the digital PPKn textbook product resulting from this research and development can become the main learning resource for students at Al-Izzah IT High School, Ciruas District. Serang, can also be a reference for other schools within the upper secondary level. This research uses the Research and Development (R&D) method using the ADDIE development model developed by Robert Marribe Branch (2009) with implementation stages including analysis, design, development, implementation and evaluation. (evaluation). The results of the material expert validation assessment were 83.6%, learning expert validation 90%, and design expert validation 97% in the Very Valid and Appropriate category. Meanwhile, the response results from teachers as users were 90% and student responses were 87.86%. Thus, the high percentage of students and teachers who gave positive responses proves that digital PPKn textbooks can be said to be effective for use to improve the civic character of class X SMA/SMK and equivalent students